Intoxication Due to Consumption of Boiled Datura Stramonium (Kecubung) Leaves - Gede Indra Dananjaya, Putu; Made Putri Purnama Dewi, Ni (International Journal of Advanced Multidisciplinary, 2024)
Datura stramonium has medicinal properties that make it suitable for treating respiratory system conditions, haemorrhoids, dermatological, for treating dental infections and toothache, skin infections, alopecia, decreasing abdomen colicky pain, and also to reduce pain. When it affects the central nervous system, it can lead to delirium symptoms such as restlessness, agitation, hallucination, convulsion, coma, and even death. Case Report: We report the case of a 59 years old, female, drink 3 glasses of boiled water of Datura stramonium leaves to reduce the pain in her waist, then she appears to be hallucinating by talking to herself. Pupil showed bilateral mydriasis. The patient got 500 cc of 0.9% NaCl in 1 hour and oxygenation. After 5 hours, the patient regained consciousness. Discussion: The presence of mydriasis, is a common symptom in nearly all cases of anti-cholinergic intoxication, including Datura stramonium. Fever and erythema may occur due to vasodilation and the inhibition of sweat glands. Additional symptoms that may occur in instances of Datura intoxication include visual hallucinations. Onset of symptoms may occur within 30-60 minutes following exposure. For the majority of patients, this condition resolves spontaneously without intervention and does not pose a risk to their lives. In severe case have resulted in respiratory failure and circulatory collapse, as well as cases of rhabdomyolysis and fulminant hepatitis. Conclusion: A comprehensive medical history and understanding of the signs and symptoms that may indicate Datura stramonium intoxication are necessary. Physostigmine, a type of cholinesterase inhibitor, is effective for treating severe case.